Water Extractable Phytochemicals from Peppers (Capsicum spp.) Inhibit Acetylcholinesterase and Butyrylcholinesterase Activities and Prooxidants Induced Lipid Peroxidation in Rat Brain In Vitro - Ogunruku, Omodesola O. (Hindawi Publishing Corporation, 2014)

(untitled) (Int J Food Sci)
Background. This study sought to investigate antioxidant capacity of aqueous extracts of two pepper varieties (Capsicum annuum var. accuminatum (SM) and Capsicum chinense (RO)) and their inhibitory effect on acetylcholinesterase and butyrylcholinesterase activities. Methods. The antioxidant capacity of the peppers was evaluated by the 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radical scavenging ability and ferric reducing antioxidant property. The inhibition of prooxidant induced lipid peroxidation and cholinesterase activities in rat brain homogenates was also evaluated. Results. There was no significant difference (P > 0.05) in the total phenol contents of the unripe and ripe Capsicum spp. extracts. Ripe and unripe SM samples had significantly higher (P < 0.05) ABTS(*) scavenging ability than RO samples, while the ripe fruits had significantly higher (P < 0.05) ferric reducing properties in the varieties. Furthermore, the extracts inhibited Fe(2+) and quinolinic acid induced lipid peroxidation in rats brain homogenates in a dose-dependent manner. Ripe and unripe samples from SM had significantly higher AChE inhibitory abilities than RO samples, while there was no significant difference in the BuChE inhibitory abilities of the pepper samples. Conclusion. The antioxidant and anticholinesterase properties of Capsicum spp. may be a possible dietary means by which oxidative stress and symptomatic cognitive decline associated with neurodegenerative conditions could be alleviated.